45-2m=3m-18

Simple and best practice solution for 45-2m=3m-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 45-2m=3m-18 equation:


Simplifying
45 + -2m = 3m + -18

Reorder the terms:
45 + -2m = -18 + 3m

Solving
45 + -2m = -18 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
45 + -2m + -3m = -18 + 3m + -3m

Combine like terms: -2m + -3m = -5m
45 + -5m = -18 + 3m + -3m

Combine like terms: 3m + -3m = 0
45 + -5m = -18 + 0
45 + -5m = -18

Add '-45' to each side of the equation.
45 + -45 + -5m = -18 + -45

Combine like terms: 45 + -45 = 0
0 + -5m = -18 + -45
-5m = -18 + -45

Combine like terms: -18 + -45 = -63
-5m = -63

Divide each side by '-5'.
m = 12.6

Simplifying
m = 12.6

See similar equations:

| 18-p=-32 | | 3x-25=4x-16 | | -25-x=19 | | x^2-4kx+k+2=0 | | 2-4kx+k+2=0 | | 19-x=25 | | 7+2X=5X-2 | | 11x-1=13y+3 | | (1+m^2)*x^2-2*m*x+1-m^2=0 | | (lgx)3=3 | | 4m=19 | | (y-z)p+(z-x)q=x-y | | X(x+5)=336 | | 3x-2+5x=8-2x+20 | | f(x)=3x^2-18x+27 | | 12x=252 | | 2tan^2x+5tanx=0 | | X-29=47 | | x^2+11.91x=2083.67 | | 624.546=81.6714*2+k | | 81.6714=624.546*2+k | | x^3-24x^2+65x-42=0 | | 1270.444=6.28*r^2+6.28*r*21.9 | | 285.9912=6.28*r^2+6.28*r*5.3 | | (3n^2)(5n^3)(2n)= | | 41=5p+11 | | 41+5p=11 | | 16x+5x=8x-5 | | n-1.6n+2.2=-4(n+5.4) | | 4.8+8.5x=x+15.7 | | (3+4)(5*5)= | | 8u+133=3u-2 |

Equations solver categories